AN ANALYSIS OF THE ROLE OF ECONOMIC ACTORS IN THE WTO DISPUTE SETTLEMENT SYSTEM - Intan Soeparna (Yuridika, 2015)
Economic actors are the main trade player in the World Trade Organization, although, the relation between WTO and economic actor is built by trade regulation that is negotiated among the WTO Members. Nothing in the WTO regulates economic actors to involve directly in the WTO, especially in the WTO dispute settlement system. Nevertheless, the debate amongst experts regarding the involvement of economic actors in the WTO dispute settlement system is unavoidable. This article therefore discusses the possibility of the involvement of economic actors in the WTO dispute settlement system, whether there is legal and political point of views. A Nation must providing broad possibility for its economic actors to conduct their activities in the large spectrum such as cross border supply and demand in the sphere of international trade in order to gain their benefits. Prior to it, state should be willing to gain economic relation in the virtue of international economic relation. An interstate economic relation is dealing with coordination of economic policies and cooperation; hence states are building rule of law in international economic relation as the prevailing part of the object of international economic law. To this end, in 1994 over one hundred governments created World Trade Organization. All WTO Members negotiated their national trade and economic policies. National trade policy is mostly implied by economic actors or individual across frontier